Humanitarianism and peace: On the (im-)possible inclusion of humanitarian assistance into peacebuilding efforts - Michael Schloms (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
The nature of intra-state conflicts and the political manipulation of humanitarian aid in the 1990s has led to the popular postulate that humanitarianism has to be included as an instrument for peacebuilding efforts. So far, the debate surrounding such a linkage has largely ignored the nature and behaviour of aid agencies. This paper focuses on the feasibility of including humanitarian action into peacebuilding strategies by taking a closer look at the reality of humanitarian organisations. Based upon the concept of peacebuilding, three sets of prerequisites for successfully combining humanitarian and peacebuilding efforts will be discussed: the compatibility of the objectives pursued in humanitarianism and peacebuilding, the perception of politics by aid agencies, and their capacity to analyse the political context of aid. The analysis highlights the heterogeneity of humanitarian actors and concludes that their contribution to peacebuilding can only be very limited. – – Als Reaktion auf innerstaatliche Konflikte und den in diesem Umfeld oft zu beobachtenden Missbrauch humanitärer Hilfe nach Ende des Kalten Krieges entstand die Forderung nach einer Einbindung humanitärer Hilfe in Peacebuilding-Strategien. Die bisherige Diskussion um solch ein synergetisches Vorgehen hat die Charakteristika humanitärer Organisationen dabei jedoch weitgehend ignoriert. Dieser Artikel geht der Frage nach, inwiefern eine Koalition aus humanitärer Hilfe und Peacebuilding machbar erscheint angesichts der Spezifika von Hilfsorganisationen. Ausgehend vom Konzept des Peacebuilding werden drei, für eine mögliche Einbindung humanitärer Hilfe in Peacebuilding wesentliche Faktoren diskutiert: Erstens, die Vereinbarkeit der Ziele und Motivationen von humanitärer Hilfe und Peacebuilding, zweitens, die von Hilfsorganisationen vorgenommene Positionierung der eigenen Arbeit in Bezug zu politischen Akteuren und zum politischen Umfeld und drittens, die Fähigkeit zur Analyse des politischen Umfelds humanitärer Hilfe. Diese Diskussion macht zum einen die Heterogenität humanitärer Akteure deutlich und kommt insgesamt zu dem Ergebnis, dass eine Einbindung humanitärer Hilfe in Peacebuilding nur äußerst begrenzt möglich ist.
Keywords: 320